International tax treatment of common law trusts : proceedings of a seminar held in New York in 1986 during the 40th Congress of the International Fiscal Association.: proceedings of a seminar held in New York in 1986 during the 40th Congress of the International Fiscal Association. (2016) - Unknown
No abstract available